On certain classes of meromorphically starlike functions - Nak Eun Cho; Ji A. Kim (International Journal of Mathematics and Mathematical Sciences)
The object of the present paper is to introduce a new class ∑n(α) of meromorphic functions defined by a multiplier transformation and to investigate some properties for the class ∑n(α) Further we study integrals of functions in ∑n(α).